Pengembangan Kemampuan Kognitif Anak dengan Menggunakan Media ATM Mainan - Desri Wahyuni; Desi Anggraini; Mezi Rahmayanti (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research is motivated by the low fine motor skills of Group B children at TK Tunas Harapan Solok Bio-Bio in Solok Bio-Bio Village. One solution to address this issue is to implement pipette folding activities. This study aims to improve fine cognitive in Group B at TK Tunas Harapan Solok Bio-Bio in Solok Bio-Bio Village. The research method used in this study is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, with two meetings in each cycle. Data collection techniques used were observation and documentation. The results of this research show an improvement in children's scores from the pre-action phase, Cycle I, to Cycle II, which can be described as follows: In the pre-action phase, 6 children or 60% had low scores (BB), then in Cycle 1, this decreased to 3 children or 30%, and in Cycle II, it became 0 children or 0%. The moderate score (MB) in the pre-action phase was 2 children or 20%, then in Cycle 1, it became 2 children or 20%, and in Cycle II, it became 0 children or 0%. The high score (BSH) in the pre- action phase was 1 child or 10%, then in Cycle 1, it became 3 children or 30%, and at 2 children or 20% in Cycle II. The very high score (BSB) in the pre-action phase was 1 child or 10%, then in Cycle 1, it became 2 children or 20%, and in the end, in Cycle II, it increased to 8 children or 80%. Based on the above research results, the researcher recommends that teachers consider implementing playing ATM activities as an alternative method to enhance children's fine cognitive Keywords: Cognitive, ATM media toy, classroom action research